Influence of serotonin on the long-term muscle contraction of the Kohnstamm phenomenon - Annika Schmidt; Tobias Meindl; Alin Albu-Schäffer; David W. Franklin; Philipp Stratmann (Scientific Reports)
Abstract Neuromodulation plays a central role in human movement control. An imbalance of neurotransmitters, especially dopamine and serotonin, can be associated with various neurological disorders causing tremors or spasms. Specifically, serotonin was shown to scale motoneuron excitability following intense muscle contractions, affecting short-latency reflexes. Likely, it may also influence motoneuron modulation in prolonged contractions, although this lacks experimental evidence. An intriguing test case for this hypothesis is presented by the Kohnstamm phenomenon, where sustained muscle contractions lead to prolonged amplified EMG activity and involuntary motions, aligning with the timescale of serotonergic amplification. The suspected serotonin influence on this effect was tested in a placebo-controlled human user study with 14 participants, where half were administered the serotonin antagonist Cyproheptadine and the other half a placebo. Comparing EMG and force responses after inducing the Kohnstamm phenomenon in the deltoid muscles revealed statistically significant faster EMG decay with the serotonin antagonist, while decay remained consistent in the placebo group compared to the response of the same participant group without medication. The force measurements showed the same trend, although no significance. This provides new data-based evidence that serotonin contributes to long-term motoneuron modulation, extending previous findings about the dedicated role and influence of this neurotransmitter. Additionally, the work suggests the phenomenon as an interesting test case to investigate the dedicated involvement of different neurocontrol mechanisms such as Persistent Inward Currents.